Quality of psychosocial services in cancer centers: Today and tomorrow. Issue 12 (12th April 2016) - Pirl, William F.; Lennes, Inga T.
Abstract : Data from Zebrack et al's survey of 57 cancer centers in the United States and Canada have led the authors to conclude that cancers centers are performing moderately well in communicating the importance of psychosocial care, identifying patient psychosocial needs, and referring patients to services. This editorial focuses on areas that need further work and places the data in the context of the process of changing practice to improve the quality of care.See also pages 1937‐45.